Analysis of The Use of A Manual Steering System On The Km Jetliner to Smoothen The Management of Ships Mounting At Kendari Port - Muhammad Fahmi Al Farishi; Dety Sutralinda; Firdaus Sitepu; I'ie Suwondo (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2026)
This study analyzes the use of a manual steering system on the KM. Jetliner in supporting smooth berthing at Kendari Port. The background of this study is based on the importance of the effectiveness of the steering system in ship maneuvers, especially in port conditions with high levels of activity. The purpose of this study is to identify the influence of the manual steering system and the factors that influence the success of berthing. This study uses a descriptive qualitative method with the research subjects of the KM. Jetliner crew who were selected purposively. The research instruments include researchers, observation guidelines, interviews, and documentation. The data analysis technique uses an interactive model in the form of data reduction, data presentation, and conclusion drawing. The results of the study indicate that the manual steering system provides a faster and more precise response than the automatic system at low speed conditions and critical berthing distances. In addition, the success of maneuvers is also influenced by crew coordination, officer experience, and support from bow thrusters and tugboats. The conclusion of this study is that the manual steering system plays a significant role in improving the safety and smoothness of berthing at Kendari Port.